2009
DOI: 10.4321/s0004-06142009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Poliorquidismo

Abstract: Although remotely, there is a possibility of malignant degeneration of these testicles, so that surgical exploration and excision of the supernumerary testicles when their biopsy is doubtful in terms of dysplasia or if they present carcinoma in situ or they are a source of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Blasius described it for the first time in 1670 as an incidental finding in an autopsy, while Lane was the one who performed the first histological description of a supernumerary testis in 1895. 1 2 Before imaging diagnosis techniques, this condition could only be verified under surgical exploration. Nowadays, current imaging techniques have increased the number of diagnosis of this anatomical variation.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Blasius described it for the first time in 1670 as an incidental finding in an autopsy, while Lane was the one who performed the first histological description of a supernumerary testis in 1895. 1 2 Before imaging diagnosis techniques, this condition could only be verified under surgical exploration. Nowadays, current imaging techniques have increased the number of diagnosis of this anatomical variation.…”
mentioning
confidence: 99%
“…However, several locations have been described at any point along the way of embryological testicular descent to its final scrotal location. 1 2 3 7 According to the literature, patient age at diagnosis ranges from 15 to 25 years, with a mean age of 17 years in the study including the largest series reported. 3 Diagnosing this malformation in childhood or in individuals over 50 is even more infrequent.…”
mentioning
confidence: 99%
See 3 more Smart Citations